1971
DOI: 10.1017/s000335610002986x
|View full text |Cite
|
Sign up to set email alerts
|

A note on the association of haemoglobin types with ewe and ram fertility and lamb mortality in Indian sheep

Abstract: SUMMARYHaemoglobin types of two Indian breeds of sheep were related to ram and ewe fertility and lamb mortality. Rams with Hb B type had a significantly higher number of lambs born to ewes mated to them. Ewe fertility and lamb mortality were better, but not significantly so, in animals with Hb B type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
2
5
0
Order By: Relevance
“…The trend was for lamb survival to be higher in lambs born to dams with Hb BB and sired by Hb AB rams and this would be consistent with the results of some workers (King et al 1958) and contrary to others (Obst & Evans 1970;Arora et al 1971;Purser & Hall 1974).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The trend was for lamb survival to be higher in lambs born to dams with Hb BB and sired by Hb AB rams and this would be consistent with the results of some workers (King et al 1958) and contrary to others (Obst & Evans 1970;Arora et al 1971;Purser & Hall 1974).…”
Section: Discussionsupporting
confidence: 86%
“…Obst & Evans (1970) found the advantage in survival of lambs from ewes with Hb AA occurred early in life and only under wet, cold conditions. Arora et al (1971) found lambs sired by rams with Hb BB had better survival than lambs sired by rams with Hb AB. Walker et al (1979), however, found no effect of ram Hb type on lamb survival.…”
Section: Introductionmentioning
confidence: 92%
“…in HbA ewes than in HbB ewes. Furthermore, the results of Arora et al (1971) and Meyer et al (1967) for sheep grazing non-oestrogenic pastures indicate similar findings.…”
Section: Discussionsupporting
confidence: 64%
“…Animals with genotype Hb and BB have been reported to have better body weight (Arora et al, 1971). In sheep, with Hb AB and Hb BB genotypes had been observed to have an effect on their performance (Dally et al, 1980;Arora, 1984;Dratch et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The study of haemoglobin polymorphism in fish has become imperative, because of its importance in the improvement of farm animals due to the fact that some polymorphic alleles may be linked with traits of economic importance (Egena and Alao, 2014). Arora et al (1971) reported marginally but not significant better body weight in Hb BB type animals.…”
Section: Introductionmentioning
confidence: 99%